Acalculous Gangrenous Cholecystitis in a Young Patient: A Case Report - Ur Rehman, Faiyyaz; Gul , Shahzore; Hanif, Kanwal; Yadav, Dipa; Khan, Imran; Roshan (Journal of Liaquat University of Medical & Health Sciences, 2024)
We present a 20 years old male with no known comorbid in emergency complaining of pain localized to the right upper quadrant for two days, followed by fever (101F) with 15-16 episodes of vomiting, which were non-bilious and containing food particles. The patient was vitally stable on examination and had a mild jaundiced look; the abdomen was soft and tender over the right hypochondrium. Ultrasound of the abdomen showed a hypoechoic liver and thick-walled acalculous gall bladder along with pericholecystic fluid, suggesting acute cholecystitis. On further evaluation, the diagnosis of gangrenous cholecystitis was made, and an emergency exploratory laparotomy along with a cholecystectomy was performed.